HEALTH PROMOTION IN FINLAND: LESSON LEARNED FROM FINNISH PEOPLE TO HEALTH PROMOTION IN THAILAND - พินิจดี พิพัฒน์พล; บัญชรหัตถกิจ พรรณี; องอาจ พัสกร (Primary Health Care Journal (Northeastern Edition), 2025)
Health promotion is a crucial process aimed at reducing health inequalities and improving quality of life. Finland and Thailand have developed health systems centered on the principles of universal health rights and disease prevention. This article provides a comparative analysis of the development and strategies of health promotion in both countries, reviewing historical case studies, health system reforms, and lessons learned from national and community-based implementation. Finland emphasizes structural reform through the establishment of Well-being Services Counties, which integrate health and social services. Key strategies focus on equity, non-communicable disease prevention, mental health, and digital health. Thailand, on the other hand, has a strong primary healthcare system through its Sub-district Health Promoting Hospitals and Village Health Volunteers. However, it faces significant challenges from the transfer of SHPHs to local government organizations and human resource constraints. Although both countries have taken different paths, they share the common goal of creating equitable and sustainable health systems. The critical questions remain: how can Finland maintain system stability amidst an aging society, and to what extent can Thailand integrate community power with policy structures to build a stronger and more sustainable health system?